Determining Factors in the Rusunawa Policy as a Liveable House for Low-Income Communities: Faktor Penentu Dalam Kebijakan Rusunawa Sebagai Rumah Tinggal Layak Huni Bagi Masyarakat Berpenghasilan Rendah - Fudiana Dwi Safitri, Afif; Fitria Agustina, Isna (Indonesian Journal of Public Policy Review, 2022)
Rental flats policy is a government policy in providing decent housing for low income people in the form of simple rental flats. However, problems in the Rental flats policy are still found, such as the limited budget resources and limited human resources. This study aims to analyze and describe factor in the Rental flats policy as a liveable house for low income people. The research method used is descriptive qualitative. Collecting data through observation, interviews, documentation and literature study. The results of the study show that resources as a determining factor in the Rental flats policy as habitable housing for low income people based on human resources and budgetary resources continue to be pursued by the Department of Housing and Settlements Cipta Karya and Spatial Planning of Sidoarjo Regency in providing services to residents of Ngelom Rental flats with the availability of human resources and budgetary resources.